2007
DOI: 10.1007/s00018-007-7175-y
|View full text |Cite
|
Sign up to set email alerts
|

Human sulfatases: A structural perspective to catalysis

Abstract: The sulfatase family of enzymes catalyzes hydrolysis of sulfate ester bonds of a wide variety of substrates. Seventeen genes have been identified in this class of sulfatases, many of which are associated with genetic disorders leading to reduction or loss of function of the corresponding enzymes. Amino acid sequence homology suggests that the enzymes have similar overall folds, mechanisms of action, and bivalent metal ion-binding sites. A catalytic cysteine residue, strictly conserved in prokaryotic and eukary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 59 publications
6
82
0
Order By: Relevance
“…The structure revealed that the overall fold of eLtaS is indeed sulfatase-like and shows striking similarity to human sulfatases and the prokaryotic Pseudomonas aeruginosa arylsulfatase (Fig. 2) (16,17). eLtaS folds into 1 hemispheric unit made up of an ␣/␤ core and a C-terminal part composed of 4 anti-parallel ␤-strands and a long ␣-helix ( Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The structure revealed that the overall fold of eLtaS is indeed sulfatase-like and shows striking similarity to human sulfatases and the prokaryotic Pseudomonas aeruginosa arylsulfatase (Fig. 2) (16,17). eLtaS folds into 1 hemispheric unit made up of an ␣/␤ core and a C-terminal part composed of 4 anti-parallel ␤-strands and a long ␣-helix ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…For PGM and sulfatases, high-resolution structures with bound substrate or substrate analogues made it possible to propose catalytic mechanisms for these enzymes (16,17). To gain similar insight into the eLtaS reaction mechanism, we cocrystallized eLtaS and an inactive eLtaS-T300A variant with glycerol-phosphate (mimicking the head group of PG) and refined the structures to 1.6-and 1.7-Å resolution, respectively [ Fig.…”
Section: Site-directed Mutagenesis Of Active Site Residues Confirms Tmentioning
confidence: 99%
“…They are located in lysosome [arylsulfatase A (ARSA), ARSB, iduronate 2-sulfatase, heparan N-sulfatase, N-acetylglucosamine-6-sulfatase, N-acetyl-galactosamine-6-sulfatase, and telethon sulfatase], endoplasmic reticulum [ARSC, ARSD, ARSF, ARSG, ARSH, ARSJ, and ARSK], Golgi apparatus (ARSE), or cell surface (sulfatase 1 and sulfatase 2) (Diez-Roux and Ballabio, 2005). Sulfatases use the formylglycine (derived from a cysteine) as the catalytic residue that attacks the sulfur atom upon activation by a water molecule (Ghosh, 2007). Due to their roles in the regulation of cell metabolism and signaling, genetic deficiencies of sulfatases result in various pathophysiological conditions such as hormone-dependent cancers, lysosomal storage disorders, and developmental abnormalities Buono and Cosma, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Arylsulfatases, for example, require the co-or posttranslational formation of a catalytically essential formylglycine (FGly) moiety to perform their hydrolysis function, removing sulfate groups from a wide array of substrates (e.g., sulfated polysaccharides, sulfolipids, and steroid sulfates) (1)(2)(3). In humans, lack of sulfatase activity can lead to disease (4), while in bacteria, inhibition impairs colonizing the mucosal layer of the host's gut (5).…”
mentioning
confidence: 99%